A natural history study of medical cannabis consumption in pediatric autism in the United States. (August 2022) - DiLiberto, Mary Ann; Zuppa, Athena F.; Cornetta, Amanda; Faig, Walter; Scully, Tryce; Bennett, Amanda; Thomas, Meghan; Ward, Elizabeth; Barr, Stephen; Yerys, Benjamin E.
Abstract: Background: Autism spectrum disorder is specifically approved for medical cannabis consumption in 20 U.S. states, the District of Columbia, and the Territory of Puerto Rico. Despite increased access, there is limited knowledge about who consumes medical cannabis, what they consume, and perceived effectiveness. We addressed these gaps by conducting a natural history study of medical cannabis consumption. Method: Children and their families engaged with a large pediatric care system were recruited to complete a telephonic study regarding their medical cannabis consumption. All children had to be consuming approved medical cannabis products issued from a state that had legalized medical cannabis for the treatment of ASD or related behaviors (irritability, hyperactivity, anxiety) ( N = 89). Results: The sample's 'level of support' and gender-ratio reflected the general autism population ( 33 % requiring 'Very Substantial Support' and 80 % male). The most common treatment targets were ASD behaviors (repetitive behaviors) and irritability. More children consumed compounds with high cannabidiol (CBD) and low or no tetrahydrocannabinol (THC). While dose did not affect overall perceived effectiveness, compounds with high-levels of CBD and low-levels of THC (CBD-dominant) were perceived as more effective than CBD-only. Conclusions: This "real world" study revealed that medical cannabis is being used to treat a wide range of behaviors. Our study also suggests that children consume CBD-rich products, and the effectiveness of CBD-dosing may be tied to the inclusion of THC in the compound. Future research should evaluate optimal dosing with a particular focus on the CBD-to-THC ratio. Highlights: Autistic children consuming medical cannabis reflected the autism population's characteristics in the United States. Common caregiver targets of medical cannabis were ASD behaviors and irritability. Most children consumed compounds high in cannabidiol (CBD). We need rigorous randomized, placebo-controlled, double-blinded clinical trials of medical cannabis for autistic children.